The complete chloroplast genome sequence of Orostachys minuta (Crassulaceae). Issue 10 (3rd October 2022) - Lee, Ha-Rim; Kim, Bo-Yun; Kang, Halam; An, Sung-Mo; Kim, Kyung-Ah; Cheon, Kyeong-Sik
Abstract: The chloroplast (cp) genome sequence is determined and analyzed for Orostachys minuta for the first time. The cp genome was 150, 369 bp in length, containing a large single-copy (LSC) of 82, 795 bp and a small single-copy (SSC) of 16, 854 bp, which were separated by a pair of 25, 360 bp inverted repeats (IRs). The overall G + C content of the O. minuta cp genome amounted to 37.7%. In total, 113 unique genes were annotated, consisting of 79 protein-coding genes (PCGs), 30 transfer RNAs (tRNAs), and four ribosomal RNAs (rRNAs). Among these genes, 18 contained one or two introns. A maximum-likelihood (ML) phylogenetic analysis based on 33 taxa showed that O. minuta formed a clade with O. japonica . This study will provide a baseline as well as valuable molecular phylogenomic information for various future studies to determine the taxonomic position and phylogenetic relationships of the genus Orostachys .